Genetic testing and surveillance in infantile myofibromatosis: a report from the SIOPE Host Genome Working Group - Hettmer, Simone; Dachy, Guillaume; Seitz, Guido; Agaimy, Abbas; Duncan, Catriona; Jongmans, Marjolijn; Hirsch, Steffen; Kventsel, Iris; Kordes, Uwe; Krijger, Ronald R. de; Metzler, Markus; Michaeli, Orli; et al. (Familial cancer, 2021)
Infantile myofibromatosis (IM), which is typically diagnosed in young children, comprises a wide clinical spectrum ranging from inconspicuous solitary soft tissue nodules to multiple disseminated tumors resulting in life-threatening complications. Familial IM follows an autosomal dominant mode of inheritance and is linked to PDGFRB germline variants. Somatic PDGFRB variants were also detected in solitary and multifocal IM lesions. PDGFRB variants associated with IM constitutively activate PDGFRB kinase activity in the absence of its ligand. Germline variants have lower activating capabilities than somatic variants and, thus, require a second cis-acting hit for full receptor activation. Typically, these mutant receptors remain sensitive to tyrosine kinase inhibitors such as imatinib. The SIOPE Host Genome Working Group, consisting of pediatric oncologists, clinical geneticists and scientists, met in January 2020 to discuss recommendations for genetic testing and surveillance for patients who are diagnosed with IM or have a family history of IM/PDGFRB germline variants. This report provides a brief review of the clinical manifestations and genetics of IM and summarizes our interdisciplinary recommendations.